IDENTIFIKASI DAN ISOLASI SENYAWA FLAVONOID EKSTRAK ETANOL DAUN GENJER (Limnocharis flava (L.) Buchenau) - Ade Ferdinan; Kurnia Audiah (Jurnal Komunitas Farmasi Nasional, 2021)
Flavonoid compounds are red, purple, blue dyes and as yellow dyes found in plants. The purpose of research to determine the kind of flavonoid compounds found in the ethanol extract of genjer leaves(Limnocharis flava (L.) Buchenau). The study was conducted by maceration extraction using 96% ethanol solvent then evaporated with a rotary evaporator so that a thick extract is obtained. The identification of flavonoid compounds was carried out by wilstater, 10% NaOH, and H2SO4 (concentrated) test. Isolation of flavonoids was done by column chromatography and identification of flavonoid compounds was done by Thin Layer Chromatography (TLC) test. Thin Layer Chromatography (TLC) results showed the presence of flavonoid compounds contained in the ethanol extract of genjer leaves (Limnocharis flava (L.) Buchenau).